Effect of Maleated Polypropylene (MAPP) on the Tensile, Impact and Thickness Swelling Properties of Kenaf Core – Polypropylene Composites - Saad, Mohamad Jani (Journal of Science and Technology, 2010)
The study on the kenaf core fiber – polypropylene (PP) composites with treated and non-treated maleated polypropylene (MAPP) was done. Epolene-43 which is commercially MAPP was used to determine MAPP’s effectiveness as a coupling agent for kenaf fiber-composites. The hot pressing system for producing kenaf core-PP composite has been used. The tensile, impact and thickness swelling results of the epolene 43 treated composite samples were better than those of the untreated composites. Scanning electron microscopy micrograph proved that the interfacial region of treated composite board shows good interaction among kenaf’s wood fiber and PP components.